An error analysis of written English paragraphs at lexical, syntactic, and paragraph levels made by Thai EFL non-English major students - Yutthasak Chuenchaichon (Penerbit Universiti Kebangsaan Malaysia, 2022)
The purpose of this study was to examine the most frequent errors made by Thai EFL non-English major students at lexical, syntactic, and paragraph levels in their EFL writing class. 95 pieces of expository paragraphs written by non- English major students who enrolled in a paragraph writing course (205122) at Naresuan University were collected and analysed. It was found that the most frequently committed errors at the word, sentence, and paragraph levels were spelling, capitalisation, and errors in semantics and good coherence, respectively. It is suggested that writing teachers utilise these errors as a facilitator in teaching and improving the writing performance of their students. In addition, L1 interference, the literal translation from Thai, and differences between Thai and English should be taken into account. Moreover, the knowledge of some particular mechanics and grammar need to be taught in greater detail. The findings emerging from the present study imply that more writing activities and exercises on revision and feedback provision are needed.